The adsorption and charge-transfer dynamics of model dye-sensitised solar cell surfaces - Mayor, Louise Charlotte (2009)
In this thesis, the dye molecule cis-bis(isothiocyanato)bis(2,2'-bipyridyl-4,4'-dicarboxylato)-ruthenium(II) (N3) is studied on the rutile TiO2(110) and Au(111) surfaces. The molecules were deposited onto the surfaces using an ultra-high vacuum (UHV) electrospray deposition system. Thermally labile molecules such as N3 cannot be deposited using the typical method of thermal sublimation, so development of this deposition technique was a necessary step for entirely in situ experiments.